Gender differences in retirement transition goals and barriers: a case study in the university sector. (2nd January 2022) - Maloney, Suzanne
ABSTRACT: Australia's retirement system is often heralded as world-class. Yet research investigating the superannuation system has reported highly gendered outcomes even in the university sector, which has generous superannuation provisions and established career management practices. This study investigates gender differences in retirement transition goals and barriers in the sector. Data from university employees who are 50 years or older show that gender differences exist. Women are more likely than men to be frustrated in their attempts to transition into retirement as desired and are more likely to desire a reduction in workdays per week. Men are more likely to prefer to continue working as currently or to reduce responsibility. Economic reasons are more likely to be the barrier for women, while organisational reasons are more likely to be the barrier for men.